Advances in Brain Inspired Cognitive Systems 6th International Conference, BICS 2013, Beijing, China, June 9-11, 2013. Proceedings - Liu, Derong; Alippi, Cesare; Zhao, Dongbin; Hussain, Amir (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Brain Inspired Cognitive Systems, BICS 2013, held in Beijing, China in June 2013. The 45 high-quality papers presented were carefully reviewed and selected from 68 submissions. BICS 2013 aims to provide a high-level international forum for scientists, engineers, and educators to present the state of the art of brain inspired cognitive systems research and applications in diverse fields.